The Malaysian Film Censorship Board / Raja Kumar - Raja , Kumar (1980)
This study outlines in brief and in desriptive from the organisational structure of the Malaysian Censorship Board. This is given in chapter II and together with it comes a brief history of the board. chapter III deals briefly on the basic and main criteria of film censorship and finally in chapter IV is given a critical outlook on the creteria’s guidelines.